Negative Effects of Calling Attention to Female Political Candidates' Attractiveness. Issue 3 (3rd July 2019) - Lizotte, Mary-Kate; Meggers-Wright, Heather J.
Abstract : Given the focus of the media on female candidate appearance in the 2008 presidential election, this research investigates the effects on voter evaluations of calling attention to female candidate attractiveness. The current research hypothesizes that pointing out candidate attractiveness likely has a negative effect on subsequent evaluations and reports of vote likelihood, particularly for female candidates. Role congruity theory, which argues that evidence of prejudice against female leaders is the result of a discrepancy between people's stereotypes of women and their stereotypes of leaders, provides an explanation for these findings. This study establishes the negative influence of calling attention to a candidate's attractiveness. In particular, a female candidate described as attractive are evaluated more negatively than a male candidate described as attractive and compared to male and female candidates, who are not described as attractive.